Muito além dos muros - Cavalheiro, Jessica Patricia (2013)
The art of dealing with the similar goes beyond simply contact a service provider to the recipient of the service , after the mouth is only part of the individual. The design PET - Saúde provides the academic experience of exploring the world beyond the walls of the college, which is simply phenomenal. This is the best way to form the dental professional with a humanist , critical and reflective view . Providing students the opportunity to encounter the reality of payphones and develop the general skills of the dentist , as communication with other professionals , experiencing multiprofessionality and transdisciplinarity , important in health promotion . During visits to municipalities were executed activities of health care with prevention and rehabilitation . Even against a background of lack of resources , lack of certain materials , common clinical presentation not prevented the carrying out of procedures and care . This experience is essential because it helps in decision making and establishment of costeffectiveness in their professional careers , based not only on scientific evidence , but also the needs of a given population . Therefore , the experience of participating in the PET allows the complete formation of the academic , also marked the Humanities and Social Sciences . Therefore, going beyond the walls of the college provides a comprehensive and humane view of the patient , which is no longer restricted to just one sick " part " , because it may have its context understood and integrated into the vision of each petiano .